A history of 20 years of medical education at Ewha Womans University College of Medicine - Ivo Kwon; Somi Jeong; Seung-Jung Kim; Ara Ko; Hyeonji Jeon (The Ewha Medical Journal)
The study aims to examine the 20-year developmental trajectory of medical education at Ewha Womans University College of Medicine (2004–2025). It analyzes educational support documents, self-evaluation reports, and Curriculum Committee meeting minutes to illuminate both the direction and significance of Ewha’s medical education reforms. Key milestones include the formal establishment of the Medical Education Office in 2004 and the subsequent founding of the Department of Medical Education in 2005. Major innovations over this period encompass the expansion of objective structured clinical examinations and the introduction of problem-based learning modules. Additional advancements include the establishment of the Ewha Medical Simulation Center and Learning Resource Center, as well as the reversion to an undergraduate medical college format in 2015. The college has also prioritized faculty development workshops and medical education seminars, implemented the Ewha Social Active Communication program, and introduced team-based learning. Noteworthy initiatives include the enhancement of student research capacity and the launch of a dedicated medical education newsletter. In 2022, the Medical Education Office was reorganized as the Ewha Center for Medical Education, marking a new era of integrated leadership and expanded educational initiatives. Ewha has consistently achieved high accreditation statuses, reflecting ongoing excellence in curriculum development, assessment, and faculty development. This progress demonstrates the dedication and collaboration of both faculty and staff, resulting in a robust educational framework. The institution’s continuous growth serves not only as a testament to past achievements but also as a foundation for future advancements in Ewha’s medical education, with the ultimate aim of cultivating women leaders in Korean healthcare.